A method for continuous preparation of water glass-based silica aerogel powder

CN122957849APending Publication Date: 2026-10-23CNCEC HUALU NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611212618.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

这些副产物残留于气凝胶孔道中,影响产品的纯度和结构性能

Benefits of technology

[0022]1.本发明发现,采用强酸性阳离子交换树脂对水玻璃进行预处理,可以有效脱除原料体系中的钠离子,降低最终产物的钠残留水平,同时获得pH为3~4的稳定酸性硅溶胶,为后续水解与凝胶反应提供均一的反应前驱体;将冷却至0℃~5℃的硅溶胶引入甲基三乙氧基硅烷与N,N-二甲基甲酰胺的混合溶液中进行水解,可以通过低温环境调控硅源的水解速率,避免水解速率过快引发的局部团聚与组分不均,获得均一透明的溶胶体系,为后续形成均匀完整的凝胶骨架提供结构基础,上述原料预处理与低温水解的技术手段相互协同,从源头上减少了杂质离子对凝胶过程的干扰,同时提升了溶胶体系的均一性,为后续湿凝胶骨架强度的提升提供了前置保障。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122957849A_ABST
    Figure CN122957849A_ABST
Patent Text Reader

Abstract

The application discloses a continuous preparation method of water glass-based silica aerogel powder, and the method comprises the following steps: taking water glass as raw material, pretreating and desodifying the water glass through strong acid cation exchange resin to obtain acid silica sol, slowly adding a mixed solution of methyl triethoxysilane and N,N-dimethylformamide into the silica sol cooled to 0-5 DEG C, and hydrolyzing the mixed solution and the silica sol together; aging the silica sol at constant temperature after the silica sol is gelled by adjusting the acidity of the silica sol to weak acidity; shearing the silica sol to prepare wet gel particles with uniform particle size; synchronously completing hydrophobic modification and solvent replacement of the wet gel particles by using a complex solution of n-hexane and trimethylchlorosilane, taking the water conductivity less than 100 mu S / cm as the reaction end point, and removing the chlorine residues through grading cleaning; and finally, realizing solvent removal, salt decomposition and skeleton shaping in stages through stepwise normal pressure drying. The method can be continuously operated, effectively inhibits skeleton shrinkage and component aggregation, reduces impurity residues, and guarantees the comprehensive performance of the product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of inorganic non-metallic porous material preparation technology, specifically to a method for continuously preparing silica aerogel powder using water glass (sodium silicate) as the silicon source through an atmospheric pressure drying process. Background Technology

[0002] Silica aerogels, due to their extremely high specific surface area, low thermal conductivity, and nanoporous structure, have broad application prospects in fields such as thermal insulation, catalysis, and adsorption. Atmospheric pressure drying (APD) is the most promising path to industrialization, replacing the high-risk, high-cost supercritical drying method. However, for the atmospheric pressure drying process using inexpensive water glass silicon sources, three technical problems remain that are difficult to solve simultaneously:

[0003] (1) Water glass (Na2SiO3) is the most cost-effective silicon source for preparing SiO2 aerogel at normal pressure, but it contains a large amount of Na. + Na + Removal of sodium is an important and costly step, and its content significantly affects sample performance. This is because sodium in water glass... + After gelation, Si-O - Na + The form is integrated into the framework, and traditional processes remove sodium by repeatedly washing with ion exchange resin or deionized water. + However, both ion exchange and repeated washing with deionized water can only remove free sodium. + Moreover, prolonged water washing consumes a lot of energy and has a long cycle, which limits large-scale production and high-end applications.

[0004] (2) Atmospheric pressure drying process requires replacing the water in the pores of the wet gel with a low surface tension solvent to prevent collapse during the drying process. Traditional process requires multiple solvent replacement steps of water → alcohol → hydrocarbon, each step requires 2 to 3 solvent exchanges, each lasting 12 to 24 hours, with a total cycle of 3 to 5 days. The solvent consumption is 5 to 10 times the gel volume, and the recovery cost is high. Existing technology has also attempted to use a one-step method with TMCS / HMDSO mixed solution to shorten the cycle, but this method is difficult to obtain a uniform bulk aerogel, and the degree of completion of the modification process is difficult to control, resulting in poor repeatability in industrialization.

[0005] (3) Simultaneously, to maintain the structure under normal pressure drying, the gel surface must be hydrophobically modified to convert hydrophilic Si-OH into hydrophobic Si-O-Si(CH3)3. During the hydrophobic modification process, different modifiers will produce different byproducts. Studies have shown that trimethylchlorosilane (TMCS) modification will generate hydrogen chloride (HCl), which reacts with ammonia or residual ammonia in the system to generate ammonium chloride (NH4Cl). Hexamethyldisilazane (HMDS) modification will generate ammonium salts, while hexamethyldisilazane (HMDSO) modification will generate water (H2O). These byproducts remain in the aerogel channels, affecting the purity and structural properties of the product.

[0006] In summary, none of the existing technologies can simultaneously solve the above three problems, making it difficult for water glass-based aerogel powders to simultaneously possess high purity, high specific surface area, and superhydrophobicity, and resulting in low production efficiency. Summary of the Invention

[0007] To address the aforementioned shortcomings in existing technologies, this invention provides a continuous preparation method for water glass-based silica aerogel powder. Using low-cost water glass as the silicon source, sodium ions are removed through pretreatment with a strongly acidic cation exchange resin to prepare an acidic silica sol. This is combined with a hydrolysis step at a low temperature of 0℃~5℃ with a mixture of methyltriethoxysilane and N,N-dimethylformamide to precisely control the sol uniformity and hydrolysis reaction rate. The aged wet gel is sheared into a wet particle suspension of a specific particle size, adapting to the continuous material transport and reaction processing procedures. The method utilizes a mixture of n-hexane and trimethylchlorosilane... The prepared modified solution simultaneously completes hydrophobic modification and solvent replacement, and uses the conductivity of the discharged water as the quantitative criterion for determining the reaction endpoint, ensuring the uniformity of modification inside and outside the particles and shortening the process flow. Finally, a multi-temperature zone stepped atmospheric pressure drying process is adopted to promote the decomposition and escape of salt in the system while maintaining the stability of the porous framework structure and hydrophobic groups, thus constructing a preparation system that can be continuously operated throughout the entire process. This solves the problems of intermittent production mode, low efficiency, high salt residue in products under atmospheric pressure drying, easy shrinkage and collapse of porous framework and easy deterioration of hydrophobic properties, and lengthy process caused by the separation of modification and solvent replacement processes in the existing technology.

[0008] To achieve the above objectives, the present invention provides a continuous preparation method for water glass-based silica aerogel powder, comprising the following steps:

[0009] Step 1: Treat water glass with a strong acid cation exchange resin to obtain a silica sol with a pH of 3-4; slowly add a mixed solution of methyltriethoxysilane and N,N-dimethylformamide dropwise to the silica sol cooled to 0℃-5℃; after the addition is complete, continue stirring and hydrolyzing for 10-30 minutes to obtain a homogeneous and transparent sol; wherein, the molar ratio of methyltriethoxysilane to SiO2 is 0.05-0.20; the molar ratio of N,N-dimethylformamide to SiO2 is 0.20-0.40; preferably, the molar ratio of N,N-dimethylformamide to SiO2 is 0.30-0.35;

[0010] Step 2: Adjust the pH of the sol prepared in Step 1 to 5.5~6.5, let it stand to gel; then, after aging treatment, obtain a wet gel; shear the wet gel to obtain a wet particle suspension with a D50 of 0.2mm~2.0mm.

[0011] Step 3: Mix n-hexane and trimethylchlorosilane to obtain a modified solution. Slowly add the wet particle suspension obtained in Step 2 into the modified solution to perform hydrophobic treatment until the conductivity of the discharged water is <100μS / cm, at which point the reaction ends. In the modified solution, the volume ratio of n-hexane to trimethylchlorosilane is (85~95):(5~15).

[0012] Step 4: After the reaction in Step 3 is completed, drain the modified liquid, add the cleaning liquid, and stir and wash at 40℃~60℃ for 5min~15min; then, wash with anhydrous n-hexane 2~3 times to remove residual alcohol and water;

[0013] Step 5: Step-by-step atmospheric pressure drying is used to promote the decomposition of NH4Cl in the byproduct into NH3 and HCl gases, thereby achieving low-temperature desalination and hydrophobicity retention, and obtaining the water glass-based silica aerogel powder.

[0014] Preferably, in step 2, the pH of the sol prepared in step 1 is adjusted with dilute ammonia water, the concentration of which is 0.5~2.0 mol / L, and the amount added is such that the pH reaches 5.5~6.5.

[0015] Preferably, in step 2, the aging conditions are: aging at 45℃~55℃ for 1h~2h.

[0016] Preferably, in step 2, the shearing conditions are: shearing at a linear velocity of 20m / s to 25m / s for 5 to 15 minutes.

[0017] Preferably, in step 3, the hydrophobic treatment process is as follows: after the wet particle suspension is slowly added to the modified liquid, the temperature is controlled at 40℃~60℃; after stirring for 30min~60min each time, stirring is stopped and the mixture is allowed to stand for 5min~10min. This stirring process is repeated 2~4 times.

[0018] Preferably, in step 4, the cleaning solution is a mixture of anhydrous ethanol and water, with a volume ratio of anhydrous ethanol to water of (60~80):(20~40).

[0019] Preferably, in step 5, the conditions for the stepped atmospheric pressure drying are as follows: under atmospheric pressure, first dry at 70℃~90℃ for 1h~3h, then raise the temperature to 140℃~160℃ for 0.5h~2h, and finally raise the temperature to 210℃~230℃ for 0.5h~2h. More preferably, under atmospheric pressure, the product obtained in step 4 is first dried at 80℃ for 2h, then raised to 150℃ for 1h, and finally raised to 220℃ for 1h.

[0020] Preferably, the tap density of the water glass-based silica aerogel powder is 0.08~0.15 g / cm³. 3 BET has a specific surface area of ​​850 m². 2 / g~1000m 2 / g, contact angle ≥140°, residual Na ≤0.5 at%, residual Cl ≤200ppm, thermal conductivity ≤0.016W / m·K.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. This invention discovers that pretreating water glass with a strongly acidic cation exchange resin can effectively remove sodium ions from the raw material system, reduce the sodium residue level in the final product, and simultaneously obtain a stable acidic silica sol with a pH of 3-4, providing a uniform reaction precursor for subsequent hydrolysis and gelation reactions. Introducing the silica sol cooled to 0-5°C into a mixed solution of methyltriethoxysilane and N,N-dimethylformamide for hydrolysis allows for the control of the silica source hydrolysis rate through a low-temperature environment, avoiding localized aggregation and component inhomogeneity caused by excessively rapid hydrolysis, resulting in a uniform and transparent sol system. This provides a structural basis for the subsequent formation of a uniform and complete gel skeleton. The aforementioned raw material pretreatment and low-temperature hydrolysis techniques work synergistically to reduce the interference of impurity ions on the gelation process from the source, while simultaneously improving the uniformity of the sol system, providing a prerequisite for improving the strength of the subsequent wet gel skeleton.

[0023] 2. This invention achieves gelation by adjusting the pH of the sol to a weakly acidic range of 5.5~6.5, and then aging it at 45℃~50℃. This promotes further cross-linking and growth of the silicon-oxygen network, strengthens the skeleton strength of the wet gel, and reduces the risk of skeleton shrinkage in subsequent modification and drying processes. Furthermore, a wet particle suspension with a D50 of 0.2mm~2.0mm is prepared by shearing at a linear velocity of 20m / s~25m / s. This yields wet gel particles with uniform particle size, ensuring sufficient contact between the particles and the modification solution during subsequent modification, improving the uniformity of the modification reaction, and meeting the material morphology requirements for continuous conveying and processing.

[0024] 3. This invention uses a modified solution of hexane and trimethylchlorosilane to hydrophobize wet particles, which can simultaneously complete solvent replacement during the grafting of hydrophobic groups, eliminating the need for a separate solvent replacement step and shortening the process flow. Using the conductivity of the discharged water <100μS / cm as the endpoint of the hydrophobication reaction, the reaction process can be quantitatively controlled, the degree of modification can be precisely controlled, and the uniformity of modification inside and outside the particles can be ensured, avoiding problems of insufficient or excessive modification. Combined with the subsequent ethanol aqueous solution and anhydrous hexane fractional washing process, residual alcohols, water and soluble by-products in the system can be gradually removed, effectively reducing the residual chloride ion content in the product.

[0025] 4. This invention discovers that by employing a stepped atmospheric pressure drying process, the solvent is slowly removed in the low-temperature range through a staged heating method, avoiding the capillary force caused by rapid solvent evaporation that damages the framework structure. In the medium-temperature range, ammonium chloride in the product is decomposed into ammonia and hydrogen chloride gas, achieving effective removal of salt. The framework is finally stabilized in the high-temperature range. Under atmospheric pressure conditions, this invention achieves a balance between low-temperature desalination and protection of hydrophobic groups, avoiding the problems of hydrophobic group decomposition and framework collapse caused by traditional high-temperature drying.

[0026] 5. In the continuous preparation method described in this invention, each process cooperates and works synergistically. The pre-removal of impurities and the regulation of the skeleton structure at the raw material end provide a stable structural basis for subsequent modification and drying. The synchronous modification and replacement and the quantitative control of the endpoint improve the process operation efficiency and modification uniformity. The step drying achieves multiple objectives of salt removal, structure maintenance and hydrophobic retention under normal pressure conditions. Ultimately, the entire preparation process can be continuously operated, while ensuring the comprehensive performance of the aerogel powder. Attached Figure Description

[0027] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0028] Figure 1 This is a schematic diagram of the continuous preparation method of water glass-based silica aerogel powder according to the present invention.

[0029] Figure 2 This is a schematic diagram of the spontaneous stratification of the system in step 3 of the present invention. Detailed Implementation

[0030] The technical solutions of this invention will be clearly and completely described below with reference to the embodiments and accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. All other embodiments obtained by those skilled in the art based on this invention are within the scope of protection of this invention. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed. Reagents or instruments whose manufacturers are not specified can be obtained commercially.

[0031] Unless otherwise specified in the specific context, the numerical ranges listed herein include upper and lower limits, as well as all integers and fractions within those ranges, and are not limited to the specific values ​​listed when defining the range. For numerical ranges, endpoint values ​​of various ranges, endpoint values ​​of various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein. The term "and / or" used herein is inclusive; for example, "A and / or B" means only A, or only B, or both A and B. Terms such as "about," "substantially the same," and similar expressions used herein indicate that reasonable deviations are permissible.

[0032] Unless otherwise specified, the experimental methods used in this invention are all conventional methods.

[0033] In the quantitative experiments of this invention, each experiment was repeated three times, and the average value of the results was taken.

[0034] I. A continuous preparation method for water glass-based silica aerogel powder

[0035] This invention addresses the issue of Na+ present during the atmospheric pressure drying process of water glass-based silica aerogel. +The three technical problems of difficult-to-remove residues, lengthy solvent replacement cycles, and the contradiction between superhydrophobic modification and impurity removal are addressed simultaneously from the following perspectives:

[0036] For Na + To address the residual problem, this invention couples the desodiuming process with the hydrophobic modification process: in a nearly alcohol-free hexane / trimethylchlorosilane system, HCl generated from the hydrolysis of trimethylchlorosilane is used to in-situ replace Si-O on the gel backbone. - Na + This allows the desodium removal reaction and the hydrophobic grafting reaction to proceed simultaneously in the same system; at the same time, after gelation, the wet gel is subjected to high-shear granulation to reduce the mass transfer characteristic size to the sub-millimeter level and shorten the ion migration path; and the conductivity of the discharged water is used as the quantitative criterion for the desodium removal endpoint.

[0037] To address the issue of lengthy solvent replacement cycles, this invention directly uses n-hexane as the dispersion medium in the hydrophobic modification and desodium removal stages, eliminating the multi-step solvent replacement process of water → alcohol → hydrocarbon in traditional processes; in the sol stage, methyltriethoxysilane is introduced for pre-hydrophobication, reducing the amount of trimethylchlorosilane used subsequently and minimizing the generation of modification byproducts; before gelation, N,N-dimethylformamide is added as a drying control agent to regulate pore size distribution, providing structural support for atmospheric pressure drying;

[0038] To address the conflict between superhydrophobicity and impurity removal, this invention further reveals that after hydrophobic modification, pure water cannot wet the pores, leading to the presence of byproducts NH4Cl and residual Na. + Residual NH4Cl affects the structure of the finished product; if high-temperature calcination (350℃) is used to remove NH4Cl, it will cause oxidation of the surface hydrophobic methyl groups (Si-CH3), resulting in loss of hydrophobicity. Therefore, this invention solves the problem from two aspects: the cleaning medium and the drying process. In the cleaning stage, a mixture of anhydrous ethanol and water is used as the cleaning medium. Ethanol is used to reduce the surface tension to overcome the capillary repulsion of the superhydrophobic channels, allowing the cleaning solution to briefly penetrate into the channels and dissolve residual NH4Cl and Na. + Simultaneously, the hydrophobic groups are prevented from being hydrolyzed and damaged by controlling the cleaning time. During the drying stage, a stepped atmospheric pressure drying process is adopted, utilizing the temperature window where the thermal decomposition temperature of NH4Cl is lower than the oxidation initiation temperature of the surface Si-CH3 groups, thus removing residual salts while maintaining hydrophobicity. Therefore, this invention designs a continuous preparation method for water glass-based silica aerogel powder, the specific steps of which are as follows:

[0039] Step 1: Treat water glass with a strong acid cation exchange resin to obtain a silica sol with a pH of 3-4; slowly add a mixed solution of methyltriethoxysilane (MTES) and N,N-dimethylformamide (DMF) dropwise to the silica sol cooled to 0℃-5℃; after the addition is complete, continue stirring and hydrolyzing for 10-30 minutes to obtain a homogeneous and transparent sol; wherein, the molar ratio of methyltriethoxysilane to SiO2 is 0.05-0.20; the molar ratio of N,N-dimethylformamide to SiO2 is 0.20-0.40; preferably, the molar ratio of N,N-dimethylformamide to SiO2 is 0.30-0.35;

[0040] Step 2: Adjust the pH of the sol prepared in Step 1 to 5.5~6.5, let it stand to gel; then, after aging treatment, obtain a wet gel; shear the wet gel to obtain a wet particle suspension with a D50 of 0.2mm~2.0mm.

[0041] Step 3: Mix n-hexane and trimethylchlorosilane to obtain a modified solution. Slowly add the wet particle suspension obtained in Step 2 into the modified solution to perform hydrophobic treatment until the conductivity of the discharged water is <100μS / cm, at which point the reaction ends. In the modified solution, the volume ratio of n-hexane to trimethylchlorosilane is (85~95):(5~15).

[0042] Step 4: After the reaction in Step 3 is completed, drain the modified liquid, add the cleaning liquid, and stir and wash at 40℃~60℃ for 5min~15min; then, wash with anhydrous n-hexane 2~3 times to remove residual alcohol and water;

[0043] Step 5: Step-by-step atmospheric pressure drying is used to promote the decomposition of NH4Cl in the product into NH3 and HCl gases, thereby achieving low-temperature desalination and hydrophobicity retention, and obtaining the water glass-based silica aerogel powder.

[0044] The continuous preparation method for water glass-based silica aerogel powder described in this invention has achieved many unexpected technical effects after practical application: the water glass-based silica aerogel powder prepared by the method described in this invention can stably reach a BET specific surface area of ​​850 m², based on the use of low-cost water glass as the silicon source and the entire process of atmospheric pressure drying. 2 / g~1000m 2 / g, tap density maintained at 0.08g / cm³ 3 ~0.15g / cm 3In the lower range of thermal conductivity, the thermal conductivity is no higher than 0.016 W / m·K, and its porous structure integrity and thermal insulation performance reach the conventional performance range of supercritical drying process. At the same time, the residual sodium content of the product does not exceed 0.5 at%, the residual chlorine content is controlled below 200 ppm, and the powder contact angle is not less than 140°. While achieving deep salt removal, the hydrophobic groups do not show obvious thermal degradation, avoiding the phenomenon of simultaneous decline in hydrophobic performance in conventional desalination processes. The low impurity residue, complete porous framework and high hydrophobic performance form a synergistic effect. The low content of alkali metal impurities reduces the risk of catalytic sintering of silicon-oxygen framework under high temperature environment, the complete pore structure provides a structural basis for low thermal conductivity, and the hydrophobic surface inhibits the pore structure damage and thermal conductivity increase caused by water vapor adsorption. Together, they endow the powder with long-term stable thermal insulation performance. Moreover, under the condition of continuous operation of the whole process, the deviation of various performance parameters of different batches of powder is small, and the batch stability is significantly better than that of traditional batch preparation process.

[0045] In some embodiments of the present invention, in step 1, DMF is used as a drying control agent to regulate the pore size distribution.

[0046] In some embodiments of the present invention, the ratio control of MTES to DMF in step 1 is a prerequisite for achieving all performance characteristics. When the MTES ratio is too low, the intrinsic hydrophobicity and mechanical strength of the skeleton are insufficient, making it unable to withstand the capillary force of atmospheric pressure drying, and also causing granulation fragmentation and a decrease in sodium removal efficiency. When the MTES ratio is too high, it will damage the stability of the sol, accelerate the gelation rate, narrow the pore size, and deteriorate the granulation performance, ultimately leading to a comprehensive deterioration of the overall performance of the product. Controlling the MTES / SiO2 molar ratio within the range of 0.05 to 0.20 is necessary to simultaneously ensure the stability of the sol system, the controllability of the gelation process, the rationality of the pore structure, and the operability of the granulation process, providing structural support for the smooth progress of subsequent sodium removal, modification, and drying processes, and also confirming the rigor and necessity of the parameter range in the present invention. Therefore, the molar ratio of methyltriethoxysilane to SiO2 is 0.05–0.20, and can be 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.13, 0.15, 0.17, 0.20, etc., as well as all ranges and sub-ranges between the above values; the molar ratio of N,N-dimethylformamide to SiO2 is 0.20–0.40, preferably 0.30–0.35, and can be 0.20, 0.23, 0.25, 0.26, 0.28, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.40, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in the embodiments, any of the above ranges can be combined with any other ranges, as long as the technical effects described in this invention can be achieved.

[0047] In some embodiments of the present invention, in step 2, the pH of the sol prepared in step 1 is adjusted with dilute ammonia water, the concentration of which is 0.5~2.0 mol / L (corresponding to 0.85%~3.4 wt%), and the amount added is such that the pH reaches 5.5~6.5.

[0048] In some embodiments of the present invention, in step 2, the aging conditions are: aging at 45℃~55℃ for 1h~2h. This temperature range can moderately accelerate the dehydration condensation reaction of residual silanol groups in the gel network, increase the crosslinking density of siloxane bonds and the strength of the backbone neck, enhance the structural rigidity and deformation resistance of the wet gel, effectively weaken the damage to the porous structure caused by subsequent shear forces, reagent penetration impacts, and drying capillary forces, reduce the risk of backbone shrinkage and collapse, and provide a structural basis for the final product to maintain a high specific surface area and low density pore structure; at the same time, the temperature and time are reasonably matched, which can avoid the problems of backbone coarsening and specific surface area reduction caused by excessive aging.

[0049] In some embodiments of the present invention, in step 2, the shearing conditions are as follows: shearing at a linear velocity of 20 m / s to 25 m / s for 5 min to 15 min, reducing the mass transfer thickness of a single particle to below 2 mm. This increases the mass transfer contact area per unit volume of material by 1 to 2 orders of magnitude compared to a whole gel, significantly reducing the mass transfer resistance of subsequent hydrophobic modifying agents and cleaning solutions diffusing into the particle's internal pores. This ensures both the depth and internal / external uniformity of the modification reaction and cleaning process, and also transforms the material into a suspension that can be continuously transported by a pump or feeding device, providing a suitable material state for continuous production throughout the entire process. Therefore, the linear velocity can be 20 m / s, 21 m / s, 22 m / s, 23 m / s, 24 m / s, 25 m / s, etc., and all ranges and sub-ranges between these values; the shearing time can be 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, etc., and all ranges and sub-ranges between these values. It should be understood that, in the implementation scheme, any of the above-mentioned ranges can be combined with any other ranges as long as the technical effects described in this invention can be achieved.

[0050] In some embodiments of the present invention, in step 3, the hydrophobic treatment process is as follows: after slowly adding the wet particle suspension to the modified liquid, the temperature is controlled at 40℃~60℃; after stirring for 30min~60min each time, stirring is stopped and the mixture is allowed to stand for 5min~10min, and this stirring process is repeated 2~4 times. This temperature range can ensure that trimethylchlorosilane has a suitable hydrolysis and condensation reaction rate, ensuring the grafting efficiency of hydrophobic groups; combined with temperature control, it can offset the violent exothermic reaction of trimethylchlorosilane with water, avoid the risk of material overflow caused by sudden temperature rise of the system, and maintain a stable and controllable reaction process. The alternating stirring and standing operation mode can utilize the density difference between the organic phase, hydrophobic gel particles and the brine phase to achieve spontaneous stratification of the system, which is convenient for accurately draining the high-density brine phase from the bottom and simultaneously replenishing an equal amount of fresh modified liquid from the top, constructing a dynamic and continuous extraction-modification system, on which Si-O is placed on the hydrogen ion replacement framework released by the hydrolysis of trimethylchlorosilane. - Na + During the simultaneous completion of surface silanol condensation grafting of hydrophobic groups, the generated salts are continuously removed from the reaction system. Specifically, the upper layer is a low-density organic phase (n-hexane / TMCS, ρ≈0.66g / cm³). 3 The middle layer has an apparent density of 0.75 g / cm³. 3 ~0.85g / cm 3 Hydrophobic gel particles (suspended at the interface), with a high-density NaCl-containing saline phase (ρ≈1.05 g / cm³) at the bottom. 3 By opening the bottom valve of the reaction equipment, the lower aqueous phase can be precisely discharged, while an equal amount of fresh modified liquid can be simultaneously replenished from the top, forming a dynamic, continuous extraction-modification process. Combined with the endpoint determination that the conductivity of the discharged water is <100 μS / cm, the degree of salt removal and the depth of hydrophobic modification can be quantitatively controlled, ensuring uniform modification inside and outside the particles and thorough salt removal. Therefore, the temperature can be 40℃, 45℃, 50℃, 55℃, 60℃, etc., and all ranges and sub-ranges between these values; the stirring time can be 30min, 35min, 40min, 45min, 50min, 55min, 60min, etc., and all ranges and sub-ranges between these values; the time for stopping stirring and allowing it to stand can be 5min, 6min, 7min, 8min, 9min, 10min, etc., and all ranges and sub-ranges between these values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range, as long as the technical effect described in this invention is achieved.

[0051] In some embodiments of the present invention, in step 4, the cleaning solution is a mixture of anhydrous ethanol and water, with a volume ratio of anhydrous ethanol to water of (60~80):(20~40). The ethanol component reduces the surface tension of the cleaning solution, overcoming the wetting barrier of the superhydrophobic channels, allowing the aqueous cleaning solution to smoothly penetrate the internal pores of the particles and fully dissolve residual soluble impurities such as ammonium chloride and sodium salts. A temperature of 40℃~60℃ increases the dissolution rate of impurities and enhances the cleaning effect. The shorter cleaning time of 5~15 min avoids prolonged contact between hydrophobic groups and the aqueous system, preventing hydrolytic degradation and maintaining the integrity of the hydrophobic structure while deeply removing residual salts. Subsequent rinsing with anhydrous n-hexane displaces residual alcohols and water from the pores, further reducing the capillary force generated by solvent evaporation during drying and minimizing the shrinkage and deformation of the porous framework.

[0052] In some embodiments of the present invention, in step 5, the conditions for the stepped atmospheric pressure drying are as follows: under atmospheric pressure, first dry at 70℃~90℃ for 1h~3h, then raise the temperature to 140℃~160℃ for 0.5h~2h, and finally raise the temperature to 210℃~230℃ for 0.5h~2h. More preferably, under atmospheric pressure, the product obtained in step 4 is first dried at 80℃ for 2h, then raised to 150℃ for 1h, and finally raised to 220℃ for 1h. The low-temperature drying stage of 70℃~90℃ can slowly remove low-boiling-point organic solvents such as n-hexane from the particle pores, avoiding the strong capillary force generated by the rapid vaporization of solvents that squeezes the framework and causes the pore structure to collapse. The medium-temperature stage of 140℃~160℃ can further remove residual alcohols and bound water, while achieving uniform temperature rise of the system, providing a smooth transition for salt decomposition in the high-temperature stage and avoiding thermal stress damage to the framework. The high-temperature stage of 210℃~230℃ can fully decompose the residual ammonium chloride in the product into ammonia and hydrogen chloride gas and escape from the system, achieving deep desalination. Moreover, this temperature is much lower than the oxidation initiation temperature of methyl groups on the aerogel surface, and will not cause thermal oxidative degradation of hydrophobic groups. Finally, under normal pressure conditions, multiple effects of maintaining the porous structure, deep salt removal and hydrophobic properties are achieved simultaneously, and high-performance aerogel powder with low impurities and high hydrophobicity can be obtained without supercritical drying equipment.

[0053] In some embodiments of the present invention, the tap density of the water glass-based silica aerogel powder is 0.08 g / cm³. 3 ~0.15 g / cm 3 BET has a specific surface area of ​​850 m². 2 / g~1000 m 2 / g, contact angle ≥140°, residual Na ≤0.5 at%, residual Cl ≤200 ppm, thermal conductivity ≤0.016 W / m·K.

[0054] II. Examples and Comparative Examples

[0055] Example 1:

[0056] Raw materials: 500mL diluted water glass (SiO2 50g, 0.832mol), 20.0mL MTES (0.100mol), 22.6mL DMF (0.291mol), MTES / SiO2≈0.12, DMF / SiO2≈0.35.

[0057] Step 1: Collect approximately 550 mL of silica sol (including deionized water used to rinse the resin column).

[0058] Step 2: Adjust the pH to 6.0 with 0.5 mol / L ammonia, gel for 8 minutes, age at 45℃ for 1.5 hours, and shear at 22 m / s for 10 minutes to obtain particles with D50≈0.8 mm.

[0059] Step 3: 400 mL of modified solution (n-hexane:TMCS=90:10), react at 50℃, stir for 45 minutes and let stand for 8 minutes as one cycle, for a total of 3 cycles, the conductivity of the water discharged in the last cycle is 85 μS / cm.

[0060] Step 4: Stir 250 mL of alcohol-water cleaning solution (ethanol:water = 75:25) at 50°C for 10 minutes.

[0061] Step 5: Under N2 atmosphere, first dry at 80℃ for 2 hours, then raise the temperature to 150℃ for 1 hour, and finally raise the temperature to 220℃ for 1 hour.

[0062] Product: White hydrophobic powder. Tap density: 0.105 g / cm³ 3 BET 929.80m 2 / g, contact angle 146.03°, Na 0.28at%, Cl 85ppm, thermal conductivity 0.0153W / m·K, average pore size 8.2nm, drying volume shrinkage <5%, granulation D50 0.8mm, <0.1mm fine powder proportion <5%, product yield >95%.

[0063] Example 2:

[0064] The method is based on Example 1, with the following adjustments: 8.3 mL (0.042 mol) of MTES, 16.1 mL (0.208 mol) of DMF, MTES / SiO2≈0.05, and DMF / SiO2≈0.25. All other steps are exactly the same as in Example 1.

[0065] Product: Tap density 0.135 g / cm³ 3 BET 902m 2 / g, contact angle 140°, Na 0.42at%, Cl 145ppm.

[0066] Example 3

[0067] The method is based on Example 1, with the following adjustments: MTES 33.3 mL (0.166 mol), DMF 12.8 mL (0.166 mol), MTES / SiO2 ≈ 0.20, DMF / SiO2 ≈ 0.20. All other steps are exactly the same as in Example 1.

[0068] Product: Tap density is 0.092 g / cm³ 3 BET is 890 m 2 / g, contact angle is 142°, Na is 0.22 at%, Cl is 78 ppm.

[0069] Comparative Example 1

[0070] The method is an adjustment based on Example 1, except that MTES is not added, only DMF is added. Therefore, in step 3, the TMCS / n-hexane volume ratio needs to be increased to 25:75 to achieve a similar hydrophobic effect.

[0071] Result: BET is 652m 2 / g, contact angle 126°, Na 0.55 at%, Cl 210 ppm. This indicates that the lack of MTES pre-hydrophobication leads to increased TMCS dosage, pore blockage, and Na... + Low removal rate.

[0072] Comparative Example 2

[0073] The modification is based on Example 1, but differs in that: in step 2, after aging, the entire gel (approximately 3×3×2cm) is directly immersed in the modification solution without stirring or draining, and soaked for 24 hours.

[0074] Result: BET is 586m 2 / g, contact angle 124°, Na 1.8 at%, Cl 380 ppm. This demonstrates that without granulation and dynamic drainage, Na... + It cannot be effectively migrated out, resulting in extremely poor performance.

[0075] Comparative Example 3

[0076] The method is based on Example 1, but with the following difference: after step 3, the alcohol and water are not washed, and the product is directly dried at 180°C for 2 hours, followed by calcination in air at 350°C for 20 minutes.

[0077] Results: Although the Cl content decreased to 92 ppm, TG-DSC analysis confirmed that the surface methyl groups began to oxidize at 320 °C, and the hydrophobicity was severely damaged at 350 °C.

[0078] Comparative Example 4

[0079] The method is adjusted based on Example 1, with the difference being the amount of MTES used. Specifically, 500 mL of water glass (containing 50 g of SiO2 and 0.832 mol of Si) is taken, and a mixture of MTES (3.3 mL, 0.0166 mol) and DMF (22.6 mL, 0.291 mol) is added dropwise. The ratio of MTES / SiO2 is approximately 0.02 (far below the lower limit of 0.05 described in this invention), and the ratio of DMF / SiO2 is approximately 0.35. The other steps are exactly the same as in Example 1.

[0080] Result: BET is 573m 2 The product has an average pore size of 5.1 nm, a tap density of 0.185 g / cm³, a thermal conductivity of 0.038 W / (m·K), a contact angle of 107°, a Na content of 0.52 at%, and a drying volume yield of 33%. The prepared product exhibits severely insufficient intrinsic hydrophobicity of the skeleton and poor particle integrity, failing to meet the process requirements of atmospheric pressure drying and simultaneous modification-removal of sodium.

[0081] Comparative Example 5

[0082] The method is adjusted based on Example 1, with the difference being the amount of MTES used. Specifically, 500 mL of water glass (containing 50 g of SiO2, Si = 0.832 mol) is used to add a mixture of 50.0 mL of MTES (0.250 mol) and 22.6 mL of DMF (0.291 mol). The ratio of MTES / SiO2 is approximately 0.30 (far higher than the upper limit of 0.20 described in this invention), and the ratio of DMF / SiO2 is approximately 0.35. The other steps are exactly the same as in Example 1.

[0083] Result: BET is 718 m 2 / g, average pore size 4.2 nm, tap density 0.142 g / cm³ 3 The thermal conductivity was 0.029 W / (m·K), the contact angle was 133°, the Na content was 0.61 at%, the granulation D50 was 0.13 mm, the proportion of fine powder <0.1 mm was 38%, the product yield was 62%, the product morphology was mostly fine powder, and some particles were dark inside; during the preparation process, the sol stability, gel controllability, pore structure, granulation performance and modification uniformity were all deteriorated, the overall performance of the product was significantly worse than that of the examples in the range of 0.05 to 0.20, and the industrial operability was poor.

[0084] As can be seen from the examples and comparative examples:

[0085] (1) All examples were prepared within a defined range of process parameters, involving a complete process including cationic resin pretreatment for sodium removal, low-temperature hydrolysis, weakly acidic gelation aging, shear granulation, simultaneous modification and sodium removal with n-hexane / trimethylchlorosilane, alcohol-water fractional washing, and stepwise atmospheric pressure drying. In Example 1, the aerogel powder obtained using an MTES / SiO2 molar ratio of 0.12 and a DMF / SiO2 molar ratio of 0.35 exhibited the best overall performance, with a tap density of 0.105 g / cm³. 3 BET has a specific surface area of ​​929.80 m². 2 / g, water contact angle 146.03°, residual sodium content 0.28 at%, residual chlorine content 85 ppm, thermal conductivity as low as 0.0153 W / m・K, drying volume shrinkage less than 5%, product yield higher than 95%. In Example 2, the molar ratios of MTES / SiO2 and DMF / SiO2 were reduced to 0.05 and 0.25, respectively, close to the lower limit of the parameter range. The product properties showed reasonable fluctuations, and the tap density increased to 0.135 g / cm³. 3 The specific surface area decreased to 902 m² 2 The contact angle remained at a superhydrophobic level of 140°, with residual sodium and chlorine contents of 0.42 at% and 145 ppm, respectively, meeting the high-performance requirements. In Example 3, the MTES / SiO2 molar ratio was increased to 0.20 and the DMF / SiO2 molar ratio was decreased to 0.20, further reducing the product tap density to 0.092 g / cm³. 3 The sodium and chlorine residues were the lowest among the three groups, at 0.22 at% and 78 ppm, respectively. The specific surface area was slightly lower than that in Example 1, at 890 m². 2 / g, with a contact angle maintained at 142°. Overall, all three sets of examples achieved a balance between high specific surface area, superhydrophobicity, and low impurity residue. The product structure integrity and thermal insulation performance reached the conventional level of supercritical drying processes, and the process was adapted for continuous operation.

[0086] (2) In Comparative Example 1, the MTES component was completely removed, leaving only DMF. To achieve a comparable hydrophobic effect, the volume percentage of TMCS in the modified solution needed to be increased to 25%. The final product had a BET specific surface area of ​​only 652 m² / g, a contact angle of 126°, and residual sodium and chlorine contents of 0.55 at% and 210 ppm, respectively, showing significant pore blockage and a decrease in sodium removal efficiency. In Comparative Example 2, the shearing granulation and dynamic drainage processes were eliminated, and the entire gel was statically soaked for 24 hours for modification. The product performance deteriorated most significantly, with a BET specific surface area of ​​only 586 m² / g. 2 / g, contact angle 124°, residual sodium as high as 1.8 at%, residual chlorine as high as 380 ppm, neither modification nor desodium removal could penetrate into the gel interior, and the porous structure was severely damaged. Comparative Example 3 omitted the alcohol-water washing step and used air calcination at 350℃ to remove salt. Although the residual chlorine could be reduced to 92 ppm, thermal analysis confirmed that the surface silanyl methyl groups underwent severe oxidative degradation at this temperature, and the product completely lost its superhydrophobic properties. Comparative Example 4 reduced the MTES / SiO2 molar ratio to 0.02, far below the lower limit of 0.05 specified in this invention. At this point, the methyl group coverage in the backbone was extremely low, and the intrinsic hydrophobicity of the gel network was severely insufficient. Although TMCS in step 3 can graft methyl groups onto the particle surface, surface modification alone cannot compensate for the hydrophilic defects within the framework. During atmospheric pressure drying, the capillary pressure generated by residual moisture in the pores cannot be effectively resisted by the weakly hydrophobic framework, ultimately leading to large-area collapse of the pores. This is manifested in a significant decrease in the BET specific surface area compared to Example 1, with the thermal conductivity increasing to 0.038 W / (m·K), and the product losing the typical low-density characteristics of aerogels. Simultaneously, insufficient cross-linking of the framework results in low mechanical strength of the gel particles, making them prone to generating numerous irregular fragments during high-shear granulation. This further exacerbates the uneven penetration path of TMCS into the particle interior during step 3, leading to a decrease in sodium removal efficiency. The sodium residue increases from 0.28 at% in Example 1 to 0.52 at%, making the overall process unsuitable for atmospheric pressure drying and simultaneous modification for sodium removal.Comparative Example 5 increased the MTES / SiO2 molar ratio to 0.30, exceeding the upper limit of 0.20, which also led to multi-dimensional performance degradation: First, loss of sol stability. Since the hydrolytic activity of MTES is much higher than that of water glass hydrolysis products, ethoxysilane can undergo slow self-condensation in a neutral aqueous environment. Excessive MTES will cause rapid condensation in some areas, fundamentally destroying the uniformity of subsequent gelation. Second, the gelation process is too fast and uncontrollable. The condensation rate of methylsilane is much higher than that of sodium silicate hydrolysis products. The excessively high proportion of MTES shortens the gelation time from about 8 minutes in Example 1 to less than 40 seconds. It is impossible to achieve uniform mixing and controllable gelation at the operational level, which is seriously inconsistent with the requirements of continuous industrial production. Third, narrowing of pore size hinders modification penetration. Excessive cross-linking reduces the average pore size of the gel from 8.2 nm to 4.2 nm. The diffusion process of TMCS in narrow channels is severely hindered, resulting in insufficient modification depth. The internal sodium ions cannot be effectively replaced, and the sodium residue increases from 0.28 at% to 0.61. at%; Fourth, the granulation performance deteriorated significantly. The excessively cross-linked gel network became more brittle, and a large amount of fine powder was generated under high shear. The proportion of particles with a diameter of less than 0.1 mm reached 38%, and the D50 was only 0.13 mm, which was far below the lower limit of 0.2 mm specified in this invention. This further led to difficulties in subsequent solid-liquid separation and a product yield of only 62%. Fifth, the thermal conductivity increased abnormally. Although the methyl content of the skeleton increased, the accumulation of fine powder increased the thermal conductivity pathways in the solid phase, and the overall thermal conductivity actually increased to 0.029 W / (m·K). This ultimately caused a comprehensive deterioration in sol stability, gel controllability, pore structure, granulation performance and modification uniformity. The overall performance of the product was significantly worse than that of the examples in the range of 0.05 to 0.20, and the industrial operability was greatly reduced.

[0087] (3) A comparative analysis of the results of the examples and the comparative examples shows that:

[0088] To address the primary technical challenge of high difficulty and cost in sodium ion removal from water glass systems, this invention constructs a multi-stage sodium removal system comprising "source pre-removal - mass transfer enhancement - reaction coupling - endpoint quantification": At the raw material end, water glass is pretreated with a strongly acidic cation exchange resin to initially remove free sodium ions and prepare an acidic silica sol with a pH of 3-4, reducing the sodium load on the system from the source; by shearing granulation, the wet particle D50 is controlled within the range of 0.2-2.0 mm, reducing the mass transfer thickness of a single particle to the sub-millimeter level, significantly shortening the migration path of sodium ions and significantly improving mass transfer efficiency; the core lies in coupling the sodium removal reaction with hydrophobic modification. In a modified system composed of hexane and trimethylchlorosilane, hydrogen ions generated in situ by the hydrolysis of trimethylchlorosilane are used to replace the bound Si-O-Na on the gel framework. +This allows desodium removal and hydrophobic grafting to occur simultaneously within the same system. Combined with a dynamic drainage mode of stirring-static stratification, the generated sodium salt can be continuously drained from the bottom of the system based on density differences, and fresh modified liquid can be added, forming a continuous extraction-reaction dynamic process. The final quantitative criterion for the desodium removal endpoint is a conductivity of less than 100 μS / cm in the drained water, precisely controlling the depth of desodium removal. Comparative Example 2, without granulation and dynamic drainage, showed that sodium ions could not effectively migrate from the entire gel, resulting in a residual amount as high as 1.8 at%, demonstrating the decisive role of mass transfer enhancement and the dynamic reaction system in desodium removal efficiency. Comparative Example 1, lacking pre-hydrophobic regulation by MTES, showed that excessive trimethylchlorosilane hydrolysis and condensation easily caused pore blockage, hindering the outward diffusion of sodium ions and leading to a decrease in desodium removal efficiency. This indicates that MTES has a synergistic supporting effect on pore structure regulation and the desodium removal process. In the final embodiment, the residual sodium content can be as low as 0.22~0.42 at%, which is far superior to the removal level of traditional repeated water washing and single ion exchange. Moreover, it does not require a lengthy multi-step water washing process, effectively solving the technical problems of high cost and long cycle of sodium ion removal.

[0089] Addressing the second technical problem of lengthy solvent replacement cycles and separate processes in traditional atmospheric pressure drying processes, this invention directly uses a mixture of n-hexane and trimethylchlorosilane as the reaction medium. Solvent replacement of water within the pores is achieved simultaneously with the grafting of hydrophobic groups, combining the traditionally separate solvent exchange and hydrophobic modification processes into one. This completely eliminates the multi-step, stepwise replacement process of water → alcohol → hydrocarbon, significantly shortening the process cycle and reducing solvent consumption. Furthermore, the sub-millimeter-sized wet particle suspension obtained by shearing and granulation possesses excellent flowability, allowing for continuous material transport via pumps. Combined with a dynamic stratified drainage reaction mode, a continuous feeding, continuous slag discharge, and continuous discharge production system can be constructed, solving the efficiency problem of traditional intermittent soaking processes. Furthermore, the MTES introduced in the sol stage can achieve pre-hydrophobication of the framework, reducing the subsequent demand for trimethylchlorosilane and decreasing the amount of modification byproducts generated from the source. DMF, as a drying control agent, can precisely regulate the pore size distribution, enhance the anti-shrinkage ability of the wet gel framework, and reduce the requirement for thorough solvent replacement during atmospheric pressure drying, further providing structural support for process simplification. Comparative Example 2 adopted a static immersion mode of whole gel, which could not achieve sufficient modification and solvent replacement even after a reaction time of 24 hours. In contrast, the example only required a few hours of multi-cycle reaction to simultaneously complete modification, desodiuming, and solvent replacement, fully demonstrating the role of process coupling and granulation enhancement in improving production efficiency and effectively solving the problems of long solvent replacement cycles, high solvent consumption, and difficulty in continuous large-scale production in traditional processes.

[0090] To address the third technical problem—the difficulty in simultaneously achieving hydrophobic modification and deep impurity removal, and the potential for byproduct residues to damage product performance—this invention addresses the contradiction between the two aspects: cleaning medium design and drying process control. In the cleaning stage, this invention uses a mixture of ethanol and water as the cleaning medium. The ethanol component reduces the surface tension of the cleaning solution, overcoming the capillary wetting barrier of the superhydrophobic channels, allowing the aqueous cleaning solution to penetrate the internal pores of the particles and fully dissolve residual soluble impurities such as ammonium chloride and sodium salts. Simultaneously, by controlling the cleaning temperature at 40-60℃ and limiting the cleaning time to 5-15 minutes, this invention ensures efficient impurity dissolution while preventing hydrophobic groups from prolonged contact with the aqueous system, thus achieving a balance between deep impurity removal and the stability of the hydrophobic structure. During the drying stage, this invention employs a stepped atmospheric pressure drying process ranging from 80℃ to 150℃ to 220℃. Utilizing the temperature window between the thermal decomposition temperature of ammonium chloride and the initial oxidation temperature of surface silanyl methyl groups, multiple objectives are achieved through staged heating: the low-temperature stage at 80℃ slowly removes the low-boiling-point n-hexane solvent, avoiding the strong capillary force generated by rapid solvent vaporization that could cause the pore structure to collapse; the medium-temperature stage at 150℃ removes residual alcohols and bound water, achieving uniform heating of the system and providing a smooth transition for salt decomposition; the high-temperature stage at 220℃ allows the residual ammonium chloride to fully decompose into ammonia and hydrogen chloride gases that escape from the system, completing deep desalination. Moreover, this temperature is far below the oxidation initiation temperature of silanyl methyl groups, preventing thermal oxidative degradation of hydrophobic groups. Comparative Example 3 used high-temperature calcination at 350℃ for desalination. Although the residual chlorine content was reduced, the surface methyl groups underwent severe oxidation, completely losing their superhydrophobicity. This demonstrates the necessity of precise temperature window control. Comparative Examples 1 and 2, lacking targeted cleaning and drying methods, both showed significantly excessive residual chlorine levels, indicating that conventional processes cannot simultaneously achieve deep desalination and preservation of superhydrophobic properties. In the examples, the residual chlorine content was as low as 78-145 ppm, while the water contact angle was consistently maintained above 140°, successfully achieving a balance between deep impurity removal and superhydrophobicity, resolving the technical problem of their mutual constraint.

[0091] In summary, this invention utilizes the low alkali metal residue resulting from deep sodium removal to reduce the catalytic sintering effect of sodium ions on the silicon-oxygen framework under high-temperature operating conditions, maintaining the long-term integrity of the porous network structure and thus ensuring long-term stability of low thermal conductivity. The high specific surface area and intact porous structure not only form the structural basis for low thermal conductivity but also provide ample reaction sites for the uniform grafting of hydrophobic groups, supporting the uniform realization of superhydrophobic properties. The superhydrophobic surface inhibits the adsorption of external water vapor into the pores, preventing pore structure damage and increased thermal conductivity caused by water vapor adsorption, while also reducing the deliquescence and migration of soluble impurities, further maintaining the purity and structural stability of the product. The low impurity residue, high specific surface area porous structure, and superhydrophobic properties mutually support and synergistically enhance each other, jointly endowing the product with excellent comprehensive performance and long-term stability, enabling the product prepared by atmospheric pressure drying to achieve performance levels approaching those of supercritical drying processes. In addition, the shearing granulation process not only enhances the reaction efficiency of sodium removal and modification by reducing the mass transfer size, but also transforms the material into a continuously transportable suspension. It is a key link connecting raw material pretreatment and downstream modification and drying, ensuring the feasibility of continuous operation throughout the entire process.

[0092] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit the technical solutions. Those skilled in the art should understand that any modifications or equivalent substitutions to the technical solutions of the present invention without departing from the spirit and scope of the present invention should be covered within the scope of the claims of the present invention.

Claims

1. A continuous preparation method for water glass-based silica aerogel powder, characterized in that, Includes the following steps: Step 1: Treat water glass with a strong acid cation exchange resin to obtain a silica sol with a pH of 3-4; slowly add a mixed solution of methyltriethoxysilane and N,N-dimethylformamide dropwise to the silica sol cooled to 0℃-5℃, and continue stirring and hydrolyzing for 10-30 minutes after the addition is complete to obtain a homogeneous and transparent sol; wherein the molar ratio of methyltriethoxysilane to SiO2 is 0.05-0.20; and the molar ratio of N,N-dimethylformamide to SiO2 is 0.20-0.

40. Step 2: Adjust the pH of the sol prepared in Step 1 to 5.5~6.5, let it stand to gel; then, after aging treatment, obtain a wet gel; shear the wet gel to obtain a wet particle suspension with a D50 of 0.2mm~2.0mm. Step 3: Mix n-hexane and trimethylchlorosilane to obtain a modified solution. Slowly add the wet particle suspension obtained in Step 2 into the modified solution to perform hydrophobic treatment until the conductivity of the discharged water is <100μS / cm, at which point the reaction ends. In the modified solution, the volume ratio of n-hexane to trimethylchlorosilane is (85~95):(5~15). Step 4: After the reaction in Step 3 is completed, drain the modified liquid, add the cleaning liquid, and stir and wash at 40℃~60℃ for 5min~15min; then, wash with anhydrous n-hexane 2~3 times to remove residual alcohol and water; Step 5: Step-by-step atmospheric pressure drying is used to promote the decomposition of NH4Cl in the product into NH3 and HCl gases, thereby achieving low-temperature desalination and hydrophobicity retention, and obtaining the water glass-based silica aerogel powder.

2. The continuous preparation method of water glass-based silica aerogel powder according to claim 1, characterized in that, In step 2, the pH of the sol prepared in step 1 is adjusted with dilute ammonia solution, the concentration of which is 0.5~2.0 mol / L.

3. The continuous preparation method of water glass-based silica aerogel powder according to claim 1, characterized in that, In step 2, the aging conditions are: aging at 45℃~55℃ for 1h~2h.

4. The continuous preparation method of water glass-based silica aerogel powder according to claim 1, characterized in that, In step 2, the shearing conditions are: shearing for 5 to 15 minutes at a linear velocity of 20 m / s to 25 m / s.

5. The continuous preparation method of water glass-based silica aerogel powder according to claim 1, characterized in that, In step 3, the hydrophobic treatment process is as follows: after the wet particle suspension is slowly added to the modified liquid, the temperature is controlled at 40℃~60℃; after stirring for 30min~60min each time, stirring is stopped and the mixture is allowed to stand for 5min~10min. This stirring process is repeated 2~4 times.

6. The continuous preparation method of water glass-based silica aerogel powder according to claim 1, characterized in that, In step 4, the cleaning solution is a mixture of anhydrous ethanol and water, with a volume ratio of (60~80):(20~40).

7. The continuous preparation method of water glass-based silica aerogel powder according to claim 1, characterized in that, In step 5, the conditions for the stepped atmospheric pressure drying are as follows: under atmospheric pressure, first dry at 70℃~90℃ for 1h~3h, then raise the temperature to 140℃~160℃ for 0.5h~2h, and finally raise the temperature to 210℃~230℃ for 0.5h~2h.

8. The continuous preparation method of water glass-based silica aerogel powder according to claim 1, characterized in that, The tap density of the water glass-based silica aerogel powder is 0.08~0.15 g / cm³. 3 BET has a specific surface area of ​​850 m². 2 / g~1000m 2 / g, contact angle ≥140°, residual Na ≤0.5 at%, residual Cl ≤200ppm, thermal conductivity ≤0.016W / m·K.